(untitled) (Agricultural Engineering, 2017)
Consumers and scientists exhibit a growing interest in bioactive ingredients of natural origin with strong pro-health effects. Such properties have been found in fruits of of Actinidia argute, commonly known as kiwiberry (mini kiwi or hardy kiwi). Appropriate methods and parameters of the drying process enable obtaining a product with preserved high pro-health properties. The obejctive of this paper was to study the influence of the selected drying methods on the drying kinetics of actinidia. Commonly known mathematical models were used to describe the process. The kinetics of convective, microwave-convective, infrared and vacuum drying was investigated. The process was performed until samples reached dimensionless moisture ratio (MR) of 0.02. The quickest method was vacuum drying reaching moisture ratio target after 286 min, and the slowest was convective drying characterized by 1352 min of drying. In general, Midilli et al.’s model was evaluated as the most adequate for description of the moisture transfer in the fruit samples.